2017
DOI: 10.1096/fj.201700186r
|View full text |Cite
|
Sign up to set email alerts
|

Targeting acetylcholine receptor M3 prevents the progression of airway hyperreactivity in a mouse model of childhood asthma

Abstract: Asthma often progresses into adulthood from early-life episodes of adverse environmental exposures. However, how the injury to developing lungs contributes to the pathophysiology of persistent asthma remains poorly understood. In this study, we identified an age-related mechanism along the cholinergic nerve-airway smooth muscle (ASM) axis that underlies prolonged airway hyperreactivity (AHR) in mice. We showed that ASM continued to mature until ∼3 wk after birth. Coinciding with postnatal ASM maturation, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 47 publications
0
15
1
Order By: Relevance
“…In the current study, we have expanded upon those findings by demonstrating that cholinergic stimulation in the absence of an inciting insult is sufficient to evoke airway hyperreactivity. Moreover, while previous studies in mice suggest that repeated cholinergic stimulation exaggerates airway narrowing in lung slices ex vivo [18], our studies in the neonatal piglet suggest that repeated stimulation is not necessary to evoke airway pathophysiology.…”
Section: Resultscontrasting
confidence: 70%
“…In the current study, we have expanded upon those findings by demonstrating that cholinergic stimulation in the absence of an inciting insult is sufficient to evoke airway hyperreactivity. Moreover, while previous studies in mice suggest that repeated cholinergic stimulation exaggerates airway narrowing in lung slices ex vivo [18], our studies in the neonatal piglet suggest that repeated stimulation is not necessary to evoke airway pathophysiology.…”
Section: Resultscontrasting
confidence: 70%
“…Lung slices were obtained from wild-type C57BL/6 mice (Jackson Laboratory, Bar Harbor, ME, USA) (Patel et al, 2017). Mice inhaled nebulized MCh (30 mg/ml) for 10 min followed by intratracheal (IT) treatment with either PEG400 (drug vehicle) or 5 mg/kg pitavastatin; treatments were repeated daily between postnatal day 15 and 20 (a total of 5 days).…”
Section: Precision Cut Lung Slicesmentioning
confidence: 99%
“…These findings emphasize early life as a critical time window for the susceptibility to asthma. Notably, NT4 −/− mice were protected from early life allergen-induced airway hyperinnervation, hypercontractility, and mucus overproduction, while having no change in airway inflammation [57••, 59]. Lineage tracing of TrkB in mice showed highly selective TrkB expression in nerves (Fig.…”
Section: Neurotrophin 4 (Nt4) and The Trkb Receptormentioning
confidence: 99%
“…Therefore, elevated NT4 levels following early life allergen exposure likely through an indirect mode of action by causing airway dysfunction through aberrant neural innervation [58••]. Functional rescue assays in NT4 −/− mice identified that the hypercontractile phenotype of ASM is caused by cholinergic hyperinnervation, while deregulated neural control of GABA secretion from PNECs is involved in mucus overproduction following early life allergen exposure [40••, 59]. Consistent with the findings in the rodent model of early life allergen exposure, children with asthma have elevated serum levels of NT4 [56].…”
Section: Neurotrophin 4 (Nt4) and The Trkb Receptormentioning
confidence: 99%